On-site ALI versus submerged culture: Chemical and toxicological investigation of brake wear sub-micrometric particles - Bozhena Tsyupa; Chiara Emma Campiglio; Elena Carrara; Marta Ripamonti; Alessandro Mancini; Andrea Bonfanti; Micol Introna; Ana Teresa Juarez-Facio; Karine Elihn; Manuela Teresa Raimondi; Andrea Remuzzi (Environmental Toxicology and Pharmacology, 2026)

Toxicity of real-world PM2.5 road tunnel emissions using a mobile air-liquid interface system and submerged exposure - Micol Introna; Ana Teresa Juárez-Facio; Naga Veera Srikanth Vallabani; Ming Hui Tu; Paavo Heikkilä; Andrea Colombo; Valentina Liboni; Bozhena Tsyupa; Alessandro Mancini; Jorma Keskinen; Ulf Olofsson; Sarah Sulamith Steimer; et al. (Environmental Pollution, 2025)

Unraveling toxicity of nanoparticles from different subway materials in lung epithelial cells and macrophages - Jana Kuhn; N.V. Srikanth Vallabani; Andrea Montano Montes; Ana T. Juárez-Facio; Micol Introna; Sarah S. Steimer; Anil Patel; Divya Bharathi Manem; Bozhena Tsyupa; Alessandro Mancini; Ulf Olofsson; Karine Elihn; et al. (Environmental Research, 2025)

An early Transcriptomic Investigation in Adult Patients with Spinal Muscular Atrophy Under Treatment with Nusinersen - Maria Liguori; Annalisa Bianco; Alessandro Introna; Arianna Consiglio; Giammarco Milella; Elena Abbatangelo; Eustachio D’Errico; Flavio Licciulli; Giorgio Grillo; Isabella Laura Simone (Journal of Molecular Neuroscience, 2024)
Spinal muscular atrophy (SMA) is a rare degenerative disorder with loss of motor neurons caused by mutations in the SMN1 gene. Nusinersen, an antisense oligonucleotide, was approved for SMA treatment to compensate the deficit of the encoded protein SMN by modulating the pre–mRNA splicing of SMN2 , the centromeric homologous of SMN1 , thus inducing the production of a greater amount of biologically active protein. Here, we reported a 10-month transcriptomics investigation in 10 adult SMA who received nusinersen to search for early genetic markers for clinical monitoring. By comparing their profiles with age-matched healthy controls (HC), we also analyzed the changes in miRNA/mRNAs expression and miRNA-target gene interactions possibly associated with SMA. A multidisciplinary approach of HT-NGS followed by bioinformatics/biostatistics analysis was applied. Within the study interval, those SMA patients who showed some clinical improvements were characterized by having the SMN2/SMN1 ratio slightly increased over the time, while in the stable ones the ratio decreased, suggesting that the estimation of SMN2/SMN1 expression may be an early indicator of nusinersen efficacy . On the other hand, the expression of 38/147 genes/genetic regions DE at T0 between SMA and HC like TRADD and JUND resulted “restored” at T10. We also confirmed the dysregulation of miR-146a(-5p), miR-324-5p and miR-423-5p in SMA subjects. Of interest, miR-146a-5p targeted SMN1 , in line with experimental evidence showing the key role of astrocyte-produced miR-146a in SMA motor neuron loss. Molecular pathways such as NOTCH, NF-kappa B, and Toll-like receptor signalings seem to be involved in the SMA pathogenesis.